2008
DOI: 10.1021/jp075809d
|View full text |Cite
|
Sign up to set email alerts
|

A New United Atom Force Field for Adsorption of Alkenes in Zeolites

Abstract: A new united atom force field was developed that accurately describes the adsorption properties of linear alkenes in zeolites. The force field was specifically designed for use in the inhomogeneous system and therefore a truncated and shifted potential was used. With the determined force field, we performed a comparative study on the adsorption behaviors of ethene and propene in four pure-silica small-pore eight-membered-ring zeolites, CHA, DDR, ITE, and IHW (named Chabazite, DD3R, ITQ-3, and ITQ-32, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 52 publications
(136 reference statements)
0
107
0
Order By: Relevance
“…The parameters in bold italics highlight those values that differ slightly from the original ones proposed by Dubbeldam et al 3 and Liu et al 4 The impact of the resulting force field differences is entirely negligible for our results, see also discussion below. Viewed from a different perspective, we can therefore state that our main conclusions, i.e.…”
Section: S6mentioning
confidence: 58%
“…The parameters in bold italics highlight those values that differ slightly from the original ones proposed by Dubbeldam et al 3 and Liu et al 4 The impact of the resulting force field differences is entirely negligible for our results, see also discussion below. Viewed from a different perspective, we can therefore state that our main conclusions, i.e.…”
Section: S6mentioning
confidence: 58%
“…The parameters we have used are shown in Figure 2 and Table 2. A similar strategy was previously used in our work on zeolites 25,26,[33][34][35] and MIL-47 (V), 23 the work of Calero and co-workers for the adsorption of CO 2 in zeolites, 36 Our computed excess adsorption isotherms as well as the experimental data 16 and previous simulation results 17 are shown in Figure 3. We found that the refined parameters yield a significantly better representation of the experimental data.…”
Section: Force Fieldmentioning
confidence: 81%
“…A similar strategy was previously used in our work on zeolites [41][42][43][44][45] and in the work of Yang and Zhong 25,34,35,46 for the adsorption of alkanes, CO 2 , N 2 , and O 2 in Cu-BTC and several other MOFs.…”
Section: Mil-47 (V)mentioning
confidence: 99%